Sharks of the Open Ocean 2008
DOI: 10.1002/9781444302516.ch7
|View full text |Cite
|
Sign up to set email alerts
|

The Biology and Ecology of the Shortfin Mako Shark, Isurus Oxyrinchus

Abstract: The shortfi n mako (Isurus oxyrinchus) is a pelagic oceanic species with a widespread distribution in temperate and tropical waters of all the world's oceans. It is a target species in some areas, but is principally caught as bycatch of longline and gill-net fi sheries directed at tuna and billfi sh. It is also an important recreational species in many regions. Reproduction is by aplacental viviparity with embryonic oophagy, and the average litter size is 12; captures of pregnant females are relatively uncommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…There is a large sexual difference in the size and age at maturity, with males maturing at about 195 cm total length (L T ) at 6 years of age, and females at 265-280 cm L T at 16 years of age (Stevens, 2008;Semba et al, 2009). While segregation among the developmental stages (Nakano and Nagasawa, 1996) and geographical sexual segregation (Mucientes et al, 2009) have been reported, little is known about stock structure or genetic diversity (Heist et al, 1996) due to the species' large, diffuse, and highly dispersive populations (Schrey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large sexual difference in the size and age at maturity, with males maturing at about 195 cm total length (L T ) at 6 years of age, and females at 265-280 cm L T at 16 years of age (Stevens, 2008;Semba et al, 2009). While segregation among the developmental stages (Nakano and Nagasawa, 1996) and geographical sexual segregation (Mucientes et al, 2009) have been reported, little is known about stock structure or genetic diversity (Heist et al, 1996) due to the species' large, diffuse, and highly dispersive populations (Schrey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The present study focuses on investigating flow over skin samples from the Shortfin Mako (Isurus oxyrinchus) as it is one of the fastest swimming marine creatures (Stevens, 2008). These scales are 0.2 mm in average size and are uniformly oriented from nose-to-tail except around pit organs and lateral lines of shark body.…”
Section: Introductionmentioning
confidence: 99%
“…It is distributed worldwide in temperate and tropical seas (Compagno 2001) and is rarely found in waters with temperatures below 13-17°C (Stevens 2008). The Shortfin Mako is an ovoviviparous species that shows oophagy.…”
mentioning
confidence: 99%